Commemorative Expectations: The Mixed-Economy Model of the Maud Lewis Painted House Preservation, 1970-1998 - Morton, Erin (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2014)
This article examines the contested commemoration of the self-taught Digby County painter Maud Lewis (1903-1970) by focusing specifically on the fate of her Marshalltown home. Following Lewis’s death in 1970, the “painted house” became a site of contest between the local community, government stakeholders, and corporate interests. The eventual installation of the house at the Art Gallery of Nova Scotia in Halifax demonstrates that the corporate influence on the AGNS and the history of neoliberal development in Nova Scotia filled the gap in federal and provincial arts funding that would have once provided assistance for such community-level initiatives as the Marshalltown conservation of the painted house.